Assessment method of the integrated thermal management system for electric vehicles with related experimental validation. (15th January 2023) - Li, Kang; Chen, Hongming; Xia, Dingyu; Zhang, Hanqi; Dou, Binlin; Zhang, Hua; Liu, Ni; Su, Lin; Zhou, Xuejin; Tu, Ran
Highlights: Electric vehicle driving conditions and component working modes are identified. An assessment method for thermal management system adaptability is proposed. Experiments verify the system performance and the evaluation method's feasibility. An integrated thermal management system with waste heat recovery and utilization is designed. The waste heat utilization vapor compression heat pump system improves mileage effectively. Abstract: Concerns about the driving ranges of electric vehicles (EV) have led to higher requirements for vehicle thermal management systems. Efficient thermal management systems should be closely integrated with the vehicle to ensure passenger comfort and maintain adequate component operating ranges. The thermal management functions should thus accurately meet the demands of the EV and its components. Based on the driving conditions for EVs and the component thermal management requirements, this study applies different working modes for the cabin, power battery, electric motor, and electric motor controller systems under various conditions, which combines these modes into 27 feasible system working modes. Subsequently, an integrated thermal management system is designed with multi-modes adjusted by each system component to adapt environmental variations by changing the system's working mode. Also, the energy exchange between components under different modes was investigated to ensure the rationality of the designed system. The best working mode is to ensure the safety and comfort for EVs with fewer components and lower cost. It was proved to meet a wide range of adaptations to environmental changes that can be used as a method to evaluate the integrated thermal management system. The method is then applied to the target thermal management system and proves that the target system offers considerable advantages over two other benchmark thermal management systems that have been used in the mass production of electric vehicles. Finally, the cooling, heating, and defrosting performances are verified experimentally, and the vehicle mileage is calculated. The thermal management system working modes are summarized systematically. The designed thermal management system is a waste heat recovery steam compression heat pump system that can meet the functional and experimental test requirements. This study verifies that the heat management system evaluation method can evaluate the system's applicability effectively and that the waste heat utilization vapor compression heat pump system can effectively improve electric vehicle driving mileage, which manifests the potential for mass production for electric vehicle applications.